Erratas sexuales. Fallas de género - Rocco Carbone (Nuevo mundo - Mundos Nuevos, 2014)
“Sexual mistakes. Fender flaws” thinks about the authoritarianism of politics and bodies and the commanding duty to access orgasm at whatever cost. From 1959 to modern day, in Paraguay, specifically. A “tour” from Stroessner's Paraguay to the contemporary Paraguay of the gender-activists movements. In that excursus, the point of interrogation –philosophical, not historical– that this work proposes, take into account some discursivities published in two diaries of 1959 –El País and El Independiente– and two Fiorello Botti’s caricatures.